Dampak kematangan emosi dengan keharmonisan perkawinan dewasa awal - Efendi, Achmad; Warsi, Nawang; Supraba, Dellawaty (UIN Maulana Malik Ibrahim Malang, 2024)
Frequent marital discord indicates disharmony between husbands and wives. Disputes cause conflicts and can lead to divorce. Kediri Regency ranks sixth for the highest divorce rate in the East Java region and has shown an increasing trend over the last five years, from 2018 to 2022. This study aims to determine the impact of emotional maturity on marital harmony among young adults in Kediri Regency. The research was conducted using quantitative methods. The measuring instruments included an emotional maturity scale and a marital harmony scale. The emotional maturity scale showed a reliability value of 0.935, while the marital harmony scale scored 0.908, indicating a high coefficient level for both scales. The study included 100 participants who met the criteria of being aged between 20 and 40 years, being married, and having a minimum of one year of marriage. A purposive sampling technique was used for participant selection. The data was analyzed using simple linear regression analysis. Based on the results of the hypothesis test, it shows that the significance value is 0.000, which shows that emotional maturity has a significant influence on marital harmony, and the R square value is 80%. This study implies that for young adult couples, creating a harmonious family through marriage requires both husband and wife to possess high emotional maturity. This can be achieved by cultivating a family environment that provides mutual mental support and encourages open communication. KEY WORDS: early adulthood; emotional maturity; martial ABSTRAK Sering terjadinya perselisihan didalam perkawinan, menandakan ketidakharmonisan antara suami dan istri. Perselisihan banyak menimbulkan konflik dan berujung dengan perceraian. Kabupaten Kediri menempati urutan ke enam untuk tingkat angka perceraian tertinggi di wilayah Jawa Timur serta cenderung naik selama lima tahun terakhir dari tahun 2018 sampai 2022. Penelitian ini bertujuan untuk memaparkan dampak kematangan emosi terhadap keharmonisan perkawinan pada dewasa awal di Kabupaten Kediri. Penelitian ini dilakukan dengan menggunakan metode kuantitatif. Alat ukur yang digunakan menggunakan skala kematangan emosi dan skala keharmonisan perkawinan. Reliabilitas pada skala kematangan emosi mendapatkan nilai 0,935 sedangkan untuk skala keharmonisan perkawinan mendapatkan skor 0,908, maka kedua skala tersebut memiliki tingkat koefisien yang tinggi. Partisipan dalam penelitian ini berjumlah 100 individu dengan kriteria individu usia 20-40 tahun dalam masa pernikahan dan usia pernikahan minimal 1 tahun. Pada penelitian ini menggunakan teknik purposive sampling untuk pengambilan sampel. Penelitian ini diolah menggunakan analisis regresi linier sederhana. Berdasarkan hasil uji hipotesis, menunjukan bahwa nilai signifikansi sebesar 0,000, hal tersebut menunjukan bahwa kematangan emosi mempunyai pengaruh yang signifikan terhadap keharmonisan perkawinan dan nilai R Square sebesar 80%. Implikasi pada penelitian ini adalah bagi pasangan dewasa awal diharapkan agar terciptanya keluarga yang harmonis dalam suatu perkawinan sebaiknya suami istri senantiasa memiliki kematangan emosi yang tinggi yakni dengan memulai dari lingkungan keluarga yang saling mendukung secara mental dan saling terbuka. KATA KUNCI dewasa awal kematangan emosi, keharmonisan perkawinan Copyright ©2024. The Authors. Published by Journal of Indonesian Psychological Science (JIPS). This is an open access article under the CC BY NO SA. link: Creative Commons — Attribution-NonCommercial-ShareAlike 4.0 International — CC BY-NC-SA 4.0